2022
DOI: 10.1002/er.8290
|View full text |Cite
|
Sign up to set email alerts
|

Production of cleaner waste tire pyrolysis oil by removal of polycyclic aromatic hydrocarbons via hydrogenation over Ni‐based catalysts

Abstract: Summary This research aimed to improve the quality of waste tire pyrolysis oil (WTPO) via hydrogenation to eliminate polycyclic aromatic hydrocarbons (PAHs), which are classified as toxic compounds or precursors to induce the formation of particulate matter. Given the presence of organosulfurous compounds in WTPO, this research was consisted of two steps. First, the hydrogenation of naphthalene, a model PAH compound, was used to screen for suitable promoters [molybdenum (Mo), tungstate (W), and platinum (Pt)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…It was widely accepted that different temper-Table 1. 27 The Si/Al of the samples from SEM-EDS. atures correspond to different acid site strengths.…”
Section: Characterization Of Supports and Supportedmentioning
confidence: 99%
See 1 more Smart Citation
“…It was widely accepted that different temper-Table 1. 27 The Si/Al of the samples from SEM-EDS. atures correspond to different acid site strengths.…”
Section: Characterization Of Supports and Supportedmentioning
confidence: 99%
“…There were two processes involved in the conversion of PAHs to AAs, hydrogenation and ring-shift isomerization reactions. , The hydrogenation of PAHs has been reported, and the corresponding mechanisms have been clearly identified. The process was a reversible process of ring-by-ring hydrogenation, , which mainly depended on the metal .…”
Section: Introductionmentioning
confidence: 99%
“…However, the elimination of PAHs in the WTPO has gained much less attention. The previous literature reported that nickel–tungsten (Ni–W) supported on γ-Al 2 O 3 had a preference for hydrogenation to eliminate PAH species in WTPO with 71.1% removal …”
Section: Introductionmentioning
confidence: 99%
“…The previous literature reported that nickel−tungsten (Ni−W) supported on γ-Al 2 O 3 had a preference for hydrogenation to eliminate PAH species in WTPO with 71.1% removal. 33 According to the complexity of chemicals in WTPO, the technique of SNAT modulation was proposed in this study to improve the modulation capability by artificial splitting-andtrapping of highly volatile compounds without the use of cryogens. The approach also enables the use of a longer 2 D column and P M and could be performed within a single injection.…”
Section: ■ Introductionmentioning
confidence: 99%